JUSTIFICATION MATHEMATICS STRATEGY OF THE 7TH GRADE STUDENT (MALE AND FAMALE) IN UNDERSTANDING CONCEPT OF GEOMETRY (TRIANGLE) - Imam Setiadi Putra (Delta: Jurnal Ilmiah Pendidikan Matematika, 2020)
This study aims to describe the mathematical justification strategies of 7th grade male and female students in understanding the concept of geometry (triangles). This research was conducted at one school in Donggo, Bima Regency, West Nusa Tenggara Indonesia in odd semester. This type of research is qualitative. The subjects involved in this study consisted of 20 students and 1 male and 1 female student were selected based on their mathematical abilities. The results of this study show that the justification by male and female students is different. So that it has different levels and types of justifications. Justifications made by male students are included in level 4 and the type of justification is Own explanation with a strategy that tends to be used, namely providing illustrations; 2) Identifying facts; 3) Formulate a plan; 4) Expressing facts; 5) Draw conclusions based on the opresari conducted .. Justifications made by male students are included in level 3 and the type of justification of Own explanation with strategies that tend to be used is 1) Identifying facts; 2) Formulate a plan; 3) Expressing facts and; 4) Draw conclusions based on the operations performed